Managing business documentation in view of its information value in Slovenian wood industry companies - Kropivšek, Jože (Zbornik gozdarstva in lesarstva, 2005)
The present competitive business environment demands more documentation, whichis also more complex for the purpose of quality execution of business operations. Documents are no longer merely bearers of information among activesubjects in business processes but have certain information value in thearchives as well. For a better control of documentation and documents themselves, availability of data and information for the need of the decision-making process in the companies, the so-called contemporary documentation management systems (DMS) and e-archives have been introduced. During our research, the current state of use of contemporary technologies andapproaches to documentation management was assessed and the quantities and recording medium for documentation storage in Slovenian wood industry companies were analysed. Documentation was classified in view of its information value and a three-level proposal of e-archive organization based on information value of documents in wood industry companies was introduced.
Keywords: elektronski arhivi; elektronsko poslovanje; lesna industrija